Jagung Berbiji Putih sebagai Bahan Pangan Pokok Alternatif - M. Yasin H.G.; Wem Langgo; Faesal Faesal (Iptek Tanaman Pangan, 2014)
White grain maize has a good potensial for an alternative staple food, because it has an affinity to rice, in terms of its physical appearance, chemical properties and taste. As apposed to the yellow maize, white maize is characterized by lacking of carotenoid pigmentasion. Indonesian Agency for Agricultural Research and Development (IAARD) had released four improved white maize varieties, namely “Anoman 1” and “Srikandi Putih 1” as open pollinated variety, and “Bima Putih 1” and “Bima Putih 2” as hybrid variety. Anoman 1 is drought tolerance, while Srikandi Putih 1 contains high protein quality, where the lysine amino acid content is twice as much as that of regular grain maize. The grain of Anoman 1 variety contains carbohydrate as much as that of rice or wheat. Growing improved variety of white maize, coupled with proper fertilization, could increase grain yield three times more compares to yield of local variety. Procedures and techniques for varietal improvement of the white maize is similar to those of regular yellow maize. Farmers group with some training could become a seed producer of an open pollinated variety, whenever the seeds are needed. Small scale farmers are suggested to grow an open-pollinated variety, but if the market demands are increasing, hybrid variety is considered feasible to be recommended. Yield potential of hybrid variety Bima Putih 1 and Bima Putih 2 is quite high, up to 10 t/ha day grain. Therefore, if the white grain maize is fully accepted for the national staple food, the national food sufficiency could be easily attained.